2014
DOI: 10.2298/jsc130819149p
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermal and surface characterization of thermoplastic polyurethanes based on poly(dimethylsiloxane)

Abstract: In this study, the synthesis, structure and physical properties of two series of thermoplastic polyurethanes based on hydroxypropyl-terminated poly-(dimethylsiloxane) (HP-PDMS) or hydroxyethoxypropyl-terminated poly-(dimethylsiloxane) (EO-PDMS) as soft segments, and 4,4′-methylenediphenyl diisocyanate and 1,4-butanediol as hard segments were investigated. The polyurethanes were synthesized by two-step polyaddition in solution. The effects of the type and content of PDMS segments on the structure, thermal and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Therefore, these results show that incorporation of PPO−PDMS segments improves thermal stability of PURs as compared to our previous synthesized PURs based on hydroxypropyl-terminated PDMS and hydroxyethoxypropyl-terminated PDMS. 37 Thermal stability of the prepared PURs based on PPO−PDMS segments is similar to thermal stability of PDMS-modified polycarbonate-based polyurethane 50 and PURs based on PPO−PDMS presented in the literature. 29 Furthermore, the obtained results have shown that the thermal degradation of the synthesized PURs, based on PPO−PDMS segments, starts at higher temperature than in the case of polyurethane based on polyether block copolymers of ethylene glycol and propylene glycol (without PDMS segments) (T 5% = 220°C).…”
Section: Resultssupporting
confidence: 72%
“…Therefore, these results show that incorporation of PPO−PDMS segments improves thermal stability of PURs as compared to our previous synthesized PURs based on hydroxypropyl-terminated PDMS and hydroxyethoxypropyl-terminated PDMS. 37 Thermal stability of the prepared PURs based on PPO−PDMS segments is similar to thermal stability of PDMS-modified polycarbonate-based polyurethane 50 and PURs based on PPO−PDMS presented in the literature. 29 Furthermore, the obtained results have shown that the thermal degradation of the synthesized PURs, based on PPO−PDMS segments, starts at higher temperature than in the case of polyurethane based on polyether block copolymers of ethylene glycol and propylene glycol (without PDMS segments) (T 5% = 220°C).…”
Section: Resultssupporting
confidence: 72%
“…All syntheses were carried out in a four‐neck, round bottom flask equipped with a mechanical stirrer, an argon inlet, a dropping funnel and a reflux condenser. The details for the synthesis of similar TPUs are given in our previously published articles . The first stage of the polyaddition was realized at 80°C for 20 min under continuous stirring, to form the NCO‐terminated prepolymer, which was considered to be obtained by reaching the theoretical –NCO content (5.75 wt %).…”
Section: Methodsmentioning
confidence: 99%
“…In the second stage of reaction, a solution of BD in DMAc/THF was added dropwise to the NCO‐terminated prepolymer and the reaction mixture was stirred and kept at 80°C for 24 h. Copolymers were precipitated into methanol/water (1/1 v/v) solution, filtered and dried to constant weight in a vacuum oven at 40°C. The yields of the copolymers after precipitation were in the range of 78–92% . The copolymer films (0.40–0.50 mm thickness) utilized for characterization and biocompatibility evaluation were cast from DMAc solution (10 wt %) into Teflon ® molds.…”
Section: Methodsmentioning
confidence: 99%
“…% hard segment have been synthesized and characterized [91,93]. FTIR, AFM and dynamic mechanic analysis (DMA) confirmed the phaseseparated structure in these copolymers.…”
Section: Poly(dimethylsiloxane)-based Biopusmentioning
confidence: 84%
“…The synthesis of PU copolymers using siloxane-containing prepolymers with PCL and ethylene oxide terminal units has been described [90][91][92][93][94][95][96][97][98]; these terminal units of siloxane-containing prepolymers were used in order to increase the miscibility of polar and non-polar reactants. Thermoplastic PU elastomers based on PDMS were synthesized by a two-step polyaddition procedure in solution, from MDI, 1,4-BD and α,ω-dihydroxy-PCL-b-PDMS-b-PCL [94].…”
Section: Poly(dimethylsiloxane)-based Biopusmentioning
confidence: 99%